(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
Sufism is an ethical behavior that entails asceticism and austerity based on the teachings of the Quran, the Sunnah, and the companions of the Prophet. There are various branches of Sufism, including practical, theoretical, and philosophical aspects that emerged in Iraq. Sufism is a dedication to obeying Allah Almighty, forsaking worldly desires, and practicing asceticism. The term "Sufism" has several possible origins, with some suggesting it comes from the Arabic word "Suf" (wool). This view is supported by scholars such as Abu Nasr al-Sarraj al-Tusi, al-Kalabazi, Abu Talib, Abu Hafs, and others. Modern scholars like Dr. Zaki Mubarak and Dr. Abdul Halim Mahmoud, as well as many orientalists like Noldeke, also endorse this origin. Others believe that the term "Sufism" comes from "Sufa," referring to a group from the pre-Islamic era who secluded themselves in devotion to Allah and resided near the Kaaba. Some connect it to words like purity, clarity, the first row, and Sufis. However, some argue that it is a distinct, non-derived term. Sufism is both a practical way of life and a spiritual upbringing rooted in religious emotion and the fervor of faith that emanates from the hearts of Muslims. The emergence of Sufism began around the end of the second century of the Islamic calendar and matured in the third century and beyond. Various opinions exist regarding Sufism. Abdul Qahir al-Baghdadi considered Sufism as an ethical behavior distinguished by the followers of the Sunnah and the community. Al-Tusi views Sufism as an action expressing an ethical phenomenon with its foundation in religion.